Impact of UV light exposure on the biocontrol efficacy of Beauveria bassiana and Metarhizium anisopliae against Bactrocera zonata - Shahid, Muhammad Zeeshan; Qayyum, Mirza Abdul; Sharif, Umer; Akhtar, Saira; Ishtiaq, Muhammad; Taha, Hasan; Shahzad, Khuram; Shan, Muhammad Aali (Journal of Agriculture and Biology, 2025)
Ultraviolet (UV) radiation and high temperatures have negative impact on persistence, pathogenicity and efficacy of entomopathogenic fungi in field conditions. This study evaluated effect of UV light, visible light and sunlight exposure on conidial viability of Metarhizium anisopliae and Beauveria bassiana at 3 intervals 15, 30 and 45 minutes. After exposure of these lights viability of conidia was evaluated through percentage germination of conidia, their pathogenicity against pupae and adult of Bactrocera zonata. In percentage germination data were collected at two time intervals of 24-27 hours and 48-51 hours after incubation. In pathogenicity test against B. zonata data of adult emergence from pupae and mortality of adult were recorded at 3, 5 and 7th day of post-treatment application. For M. anisopliae untreated control had showed highest conidial germination (50.83% at 24–27 hours, 87.17% at 48–51 hours) while UV-45 exposure reduced it to 16.50 % and 35.50% respectively. For B. bassiana germination was highest in the untreated control (30.17% and 50.83%) and lowest in UV-45 (8.50% and 22.50%). In case of M. anisopliae untreated control provided highest mortality of adults 62.2% at 3rd day, 80.00% at 5th day and 91.1% at 7th day. Lowest was in case of UV light treatment, 4.4% at 3rd day, 11.1% at 5th day and 13.3% at 7th day. Adult emergence was highest from pupae after UV light treatment, 57.8% at 3rd day, 68.9% at 5th day and 80.00% at 7th day. Lowest was in case of untreated control, 17.8% at 3rd day, 28.9% at 5th day and 37.8% at 7th day. In case of B. bassiana untreated control provided highest mortality of adults 44.4% at 3rd day, 57.8% at 5th day and 71.1% at 7th day. Lowest was in case of UV light treatment, 2.2% at 3rd day, 6.7% at 5th day and 11.1% at 7th day. Adult emergence was highest from pupae after UV light treatment, 42.2%at 3rd day, 57.8% at 5th day and 62.2% at 7th day. Lowest was in case of untreated control, 13.3% at 3rd day, 22.2% at 5th day and 26.7% at 7th day. The untreated control without light exposure gives maximum control of B. zonata and has a maximum pathogenicity because conidia viability was not affected with exposure to any light stress. In the comparison UV light caused more damage to the fungal conidia following sunlight and visible light respectively. Moreover, 45 minutes’ exposures were most damaging than 30 and 15 minutes. This study highlighted the detrimental effect of UV light concluded that these EPF can be effective in shaded areas of orchard against B. zonata.
Keywords: UV light; conidial germination; Entomopathogenic fungi; Fruit fly; microbial control